High pressure rheology: a probe for formulation development - Pepper, Katie Jayne (2019)
The development of new routes for therapeutic delivery such as controlled or sustained delivery systems, is time and cost consuming. This is because it is necessary to perform multiple in vitro dissolution studies to investigate the release profiles of all the formulations in the early stages of development. This thesis aims to investigate the potential use of rheology as a pre-screening tool to aid formulation development by reducing the number of in vitro studies that need to be performed. The hypothesis being that rheology could be used to assess the homogeneity and processability of a formulation, with the expectation that a homogeneous formulation would exhibit consistent release profiles on a batch-to-batch basis. Recent advances in pharmaceutical research have identified supercritical carbon dioxide (scCO2) as a potential green solvent alternative for the production of microparticles that promote the sustained release of APIs (active pharmaceutical ingredients) from a polymer matrix. Mild conditions are necessary to preserve the integrity of the API and carbon dioxide (CO2) is well documented to be able to reduce the viscosity of polymers at low temperatures. In order to quantify this, a robust and reliable rheology method was established to measure the polymer melt viscosity in the presence of CO2. First, the viscosity of the single polymers: polycaprolactone (PCL112) and poly(D,L-lactide) (PLA11), in their molten states was measured at ambient pressure and in the presence of CO2. For simplicity these measurements were made at elevated temperature (80-90 °C), where the samples were already molten at ambient pressure. However, this method was not suitable for formulations containing thermosensitive APIs, such as proteins or peptides, because they degrade at temperatures above physiological conditions (> 40 °C). Therefore, the method was adapted for use at lower temperatures by exposing the polymers to 140 bar of CO2 at 40 °C, without preheating. Although CO2 is known to reduce the viscosity of polymers it has been shown that the polymer melt viscosity remains relatively high, hindering the incorporation and even distribution of the drug. Additives such as plasticisers can be used to optimise the viscosity and processing parameters of a pharmaceutical formulation. Poly(ethylene glycol) (PEG) has been employed extensively as a polymeric plasticiser for Poly(lactic acid) (PLA) and as an excipient in pharmaceutical formulations. It was thought that by combining both the plasticising effects of CO2 and PEG it would be possible to further reduce the viscosity of PLA. This was not the case; however, a reduction in the time taken for the samples to reach their saturation viscosity was observed. The effect of the mode of PEG incorporation was also investigated, where PEG as a blended excipient was compared to PEG as a covalently linked entity in a block copolymer. The plasticising effect was found to have similar efficiency regardless of the incorporation method. Finally, a series of formulations containing a model protein drug, bovine serum albumin (BSA) encased in a polymer matrix were produced using a CO2 mixing procedure. The influence of the composition of the polymer matrix was investigated and a mix of PD,LLA and PLGA was found to be the most suitable. The effect of BSA content, BSA particle size and polymer ratio on the rheological properties and the release profiles was evaluated. A content assay and micro Raman spectroscopy were performed to assess the API content and the homogeneity of the formulations. It was expected that a formulation that can be readily processed will have a homogenous distribution of API and would exhibit consistent release profiles on a batch-to-batch basis. An in vitro dissolution study was performed on the formulations and the results were compared to the rheological data. It was found that if the rheology of a formulation could be measured and analysed and the viscosity was sufficiently low, then this formulation should exhibit consistent release profiles across different batches. Overall, this thesis aims to determine whether high pressure rheology can be used as an aid for formulation development. The data show that it is possible to measure the viscosity of complex formulations in a robust and reliable manner. These preliminary data suggest there is a general correlation between the rheological properties of a formulation and the consistency of its in vitro release.